BMT'S TRANSFORMATION: TOWARDS A SUSTAINABLE INCLUSIVE FINANCIAL MODEL - Maryani Ayu Rahma; Putri Damayanti; Rinda Asytuti (JASIE, 2024)
This study discusses BMT's strategy in transforming to support inclusive and sustainable finance using qualitative methods and theapproach in this study is a content analysis study. The result of this study is that every financial institution in Indonesia uses an inclusive financial system, because with this inclusive finance makes an easy requirement which means that people from the lower class can access and use existing facilities easily because of easy requirements.